Kakovost življenja starostnikov v domskem varstvu - Gašparovič, Marta (Obzornik zdravstvene nege, 1999)
The article brings a survey of foreign literature from the field of quality oflife in old people's homes. Different research approaches and quality measurement methods are described. Individual concept of approach to an old person which is of vital importance for the quality of his/her life is described. Individual concept of approach covers four basic areas: the importance of old people's autonomy and dignity; self reliance and self care; health education of the old person and his/her family; team work. All this present a different approach to life of old people in old people's homes.
Keywords: Aged; domovi za stare ljudi; Health education; Homes for the aged; kvaliteta življenja; Quality of life; Self care; starostniki